ANALYSIS OF INFLATION, PURCHASING POWER, AND ECONOMIC GROWTH DURING A PANDEMIC - Irwan Moridu; Aris Munandar; Rully Movie Wurarah; Luckhy Natalia Anastasye Lotte; , Roikhan Mochamad Aziz (Bajang Institute, 2022)
The purpose of this study to discuss about analysis of inflation, purchasing power, and economic growth during a pandemic. This research uses descriptive qualitative. This research data uses secondary data. Data analysis used qualitative data analysis. The research results show that efforts to control inflation involving the government and all relevant stakeholders managed to keep inflation at the level of 1.68 percent in 2020. Until 2021, inflation is still quite low and prices of basic necessities are quite stable. The national economy will continue to strengthen with gross domestic product in quarters I-II 2022 positive growth. The spread of the new variant of Omicron, which was feared to be a constraint to the national economy, could be overcome by starting the 3rd phase of the vaccine, namely booster. Public purchasing power continues to improve, marked by stronger growth in household consumption and national employment conditions.